Review of: "The Failure of Public Water Utility Privatization From Araral’s Perspective: Implications for Ethiopia’s Water Sector" - Ariva Sugandi Permana (My University, 2023)
Reading the title of the article I have a mixed impression, positive and negative impressions.The positive impression is that the privatization of public goods is always challenging
Keywords: Water Governance and Infrastructure; Water resources management and optimization; Child Nutrition and Water Access